Electrochemical Promotion of Non-Noble Metal Catalysts for the Reverse Water Gas Shift Reaction - Wang, Ju (Université d'Ottawa | University of Ottawa, 2024)
The greenhouse gas carbon dioxide (CO2) can be transformed into carbon monoxide (CO) via the reverse water gas shift (RWGS) reaction. This process not only mitigates CO2 emissions but also recycles it into valuable chemicals, as CO is an essential precursor in hydrocarbon production through the Fischer-Tropsch process. Nanostructured metals immobilized on oxide supports serve as catalysts for this reaction, where the formation of metal-support interactions (MSI) influence both catalytic performance and thermal stability. Additionally, the catalytic activity can be regulated and modified through the electrochemical promotion of catalysis (EPOC), also known as non-Faradaic electrochemical modification of catalytic activity (NEMCA) by applying electrical potential or current across the catalyst deposited on solid electrolyte. In pursuit of a cost-effective and high-performance EPOC system, copper (Cu) is investigated as a promising non-noble metal catalyst for the RWGS reaction due to its affordability, high activity, and selectivity. When deposited on yttria-stabilized zirconia (YSZ) solid electrolyte, the electrochemical polarization at +2V leads to the migration of oxygen ions (O2-) toward Cu, inducing its partial oxidation from Cu0 to Cu1+ and enhancing the reaction rate by 20%. Non-noble metal oxides such as cobalt oxide (Co3O4) and zinc oxide (ZnO) are explored as supports for Cu to prevent its deactivation due to oxidation and sintering at elevated temperatures. Co3O4, in particular, acts as an active phase and an oxygen reservoir in the Cu/Co3O4 co-catalyst. Under positive potential, O2- transfer from Co3O4 to Cu decreases the reaction rate by 42%, while the reverse process at negative potential increases it by 16%. Additionally, studies on Cu/ZnO catalysts with Cu loadings between 5 to 60 wt.% confirm that ZnO effectively prevents Cu from sintering and complete oxidation, and the MSI between Cu and ZnO improves the catalytic rate by 75%. Under positive polarization at +400μA, all catalysts exhibit EPOC effects, with 10Cu/ZnO showing the largest increase of 14%. Density functional theory (DFT) modelling further investigates the migration of O2- from ZnO to Cu and the subsequent formation of Cu2O. A correlationis established between the electrochemical active surface area (ECSA) and the magnitude of the EPOC effect, offering insights into the selection of suitable oxide supports for EPOC studies. To expand the application of EPOC to reactions favorable at lower temperatures, a lithium-ion (Li+) conductor, lithium lanthanum titanate (LLTO), is introduced as an alternative solid electrolyte because of its high ionic conductivity at reduced temperatures. For the first time, Li+ is shown to act as a promoter of catalytic RWGS reaction and CO oxidation in EPOC experiments. Unique interactions between Li+ and metal/metal oxide catalysts using platinum (Pt) and iron-oxide (FeOx) are revealed, enabling EPOC to drive CO oxidation at temperatures as low as 150°C. The MSI between FeOx and LLTO also enhances the RWGS catalytic rate, making it 3 times higher compared to FeOx deposited on YSZ. This discovery opens new possibilities for practical EPOC applications in energy conversion processes. Physicochemical characterizations, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), Brunauer-Emmett-Teller (BET) analysis, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), are conducted to analyze the morphology, size, elemental composition, specific surface area, crystallite structure, and oxidation state of the metal catalysts. Electrochemical characterization through cyclic voltammetry (CV) provides in-situ insights into the interactions between the metal catalysts and ionic species from the solid electrolyte.
Keywords: electrochemical promotion of catalysis; reverse water gas shift reaction; nanocatalyst; metal support interaction; copper nanoparticles; lithium-ion promoter; density functional theory